A COMPARATIVE ANALYSIS OF PREPAID AND POSTPAID KWH METERS IN IMPROVING ACCURACY OF ELECTRICITY USAGE MEASUREMENTS TO CUSTOMER SERVICE UNIT (ULP) CUSTOMERS PT PLN IN PEUREULAK, EAST ACEH - Sarita, Rahma; Tarigan, Adisastra Pengalaman; Anisah, Siti (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the comparison of prepaid and postpaid KWH meters in improving the accuracy of electricity usage measurements for customers of PT PLN's Customer Service Unit (ULP) in Peureulak, East Aceh. The prepaid system allows customers to control electricity usage based on previously purchased power, while the postpaid system records electricity consumption that will be billed after a certain period. This study was conducted through collecting primary and secondary data from customers and comparative analysis of the level of measurement accuracy, efficiency, and customer satisfaction. The results of the study indicate that the prepaid KWH meter system has a better level of accuracy compared to the postpaid system, especially in reducing the risk of incorrect manual recording and increasing transparency of electricity usage. These findings are expected to be a consideration for PT PLN in improving services to customers and encouraging the implementation of the prepaid system more widely.